Overview of single-input single-output distillation control - Mohd. Yusof, Khairiyah (Faculty of Chemical & Natural Resources Engineering, 1992)
Distillation is a very important operation in the chemical industry. Distillation columns are notoriously known for being difficult to control. This paper presents an overview of distillation control for a general understanding of the important aspects that influence single-input single-output control of a column.